Perlindungan Hukum Terhadap Korban Kejahatan Pada Proses Penyelidikan Dan Penyidikan Dalam Sistem Peradilan Pidana - Yulia, Rena; Herli, Dadang; Prakarsa, Aliyth (UI Scholars Hub, 2019)
The police is the first and main gate in the process of law enforcement. Crime victims will report or complain about the criminal incident they experienced to the police. For reports or complaints of victims, the police will conduct an investigation to find and even that is suspected of being a criminal offense in order to determine whether or not an investigation can be conducted. In the process of investigation, victims are often treated as witnesses, or even reported. Victims are given entrapment questions and the attitude of the police treat victims not as victims. The victim becomes secondary victimization. This paper will examine how legal protection for crime victims on police investigation process in criminal justice system.